Les initiatives d’adaptation aux changements climatiques - François Bertrand; Elsa Richard (Territoire en Mouvement)
Territorial issues of climate change, related to anthropogenic greenhouse effect, are fluctuating both in their expressions and in their effects. Territories are unequal to these climate changes both in terms of exposure to the effects (depending on physical, social, economic, cultural factors, etc.) and in terms of responsiveness (ability of apprehension, anticipation, repair, etc.). Local climate change adaptation management may accentuate some disparities between territories, but some initiatives of "pooling" and horizontal cooperation are also observed. This article intends to discuss how the development and implementation by local authorities of “climate adaptation policy” are part of the decrease of regional disparities as a classical planning objective (Choay and Merlin, 1988). In particular, does local management of the effects of CC enhance the mechanisms of cooperation and solidarity or does it pursue the current dynamics of competition between the territories? This paper is based on the results of several research projects, completed or in progress, on local initiatives related to the challenge of CC and led mainly in France. After a theoretical presentation of the main territorial disparities to climate change, in terms of both exposure and adaptive capacity (1), this paper will develop an analysis of the evolution of territorial adaptation measures seen, on the first hand, as a continuation of the existing discourse on territorial development, focused on enhancing the competitiveness and attractiveness of major urban centers (2). And on the other hand, issues related to a better understanding of the impacts of CC seem to be able to initiate or extend the dynamics of territorial cooperation and the creation of new “scenes of discussion” (3).